2017
DOI: 10.15408/aiq.v9i2.5153
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Efficiency and Productivity in Islamic Banking : Case Study Indonesia, Malaysia and Pakistan

Abstract: Comparing Efficiency and Productivity in Islamic Banking: Case Study in Indonesia, Malaysia, and Pakistan. The objective of this research is to analyze both efficiency and productivity of Islamic Banking Industry in Indonesia, Malaysia and Pakistan. The technique that used in this research is Data Envelopment Analysis (DEA) as for measuring efficiency and thus Malmquist Index (MI) as for measuring productivity. The result of this research found that Islamic Banking Industry in Indonesia is facing inefficiency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 3 publications
2
19
0
Order By: Relevance
“…On the other hand, Rodoni et al [49] undertook a comparison of the productivity and efficiency of the Islamic banking sector between 2009 and 2013 in Pakistan, Indonesia and Malaysia; the data included 31 banks across these three countries. Using the Malmquist productivity index (MPI) to gauge productivity and Data Envelopment Analysis (DEA) in gauging efficiency the findings from the study found that the efficiency of the sector in Malaysia was far better compared to Indonesia while in Pakistan, the rate of efficiency was near to 100% during this period.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, Rodoni et al [49] undertook a comparison of the productivity and efficiency of the Islamic banking sector between 2009 and 2013 in Pakistan, Indonesia and Malaysia; the data included 31 banks across these three countries. Using the Malmquist productivity index (MPI) to gauge productivity and Data Envelopment Analysis (DEA) in gauging efficiency the findings from the study found that the efficiency of the sector in Malaysia was far better compared to Indonesia while in Pakistan, the rate of efficiency was near to 100% during this period.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, few studied have discussed the productivity analysis of social funds in Islamic banks. In the term of productivity analysis, the Islamic banks' productivity continues to increase (Afiatun & Wiryono, 2010;Arjomandi et al, 2012;Rodoni et al, 2017). After spinning off, Islamic banks also increased their productivity (Norfitriani, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Adawiyah (2015) found that there are no efficiency differences between Islamic banks and foreign banks. Rodoni et al (2017) concluded that the Indonesian Islamic banking industry is less efficient rather than Islamic banking sector in Malaysia and Pakistan.…”
mentioning
confidence: 99%